Parenting Stress, Mental Health, Dyadic Adjustment: A Structural Equation Model - Rollè, Luca; Prino, Laura E.; Sechi, Cristina; Vismara, Laura; Neri, Erica; Polizzi, Concetta; Trovato, Annamaria; Volpi, Barbara; Molgora, Sara; Fenaroli, Valentina; Ierardi, Elena; Ferro, Valentino; et al. (Frontiers in Psychology, 2017)
Objective: In the first year of the postpartum period, parenting stress, mental health, and dyadic adjustment are important for the wellbeing of both parents and the child. However, there are few studies that analyze the relationship among these three dimensions. The aim of this study is to investigate the relationships between parenting stress, mental health (depressive and anxiety symptoms), and dyadic adjustment among first-time parents. Method: We studied 268 parents (134 couples) of healthy babies. At 12 months postpartum, both parents filled out, in a counterbalanced order, the Parenting Stress Index-Short Form, the Edinburgh Postnatal Depression Scale, the State-Trait Anxiety Inventory, and the Dyadic Adjustment Scale. Structural equation modeling was used to analyze the potential mediating effects of mental health on the relationship between parenting stress and dyadic adjustment. Results: Results showed the full mediation effect of mental health between parenting stress and dyadic adjustment. A multi-group analysis further found that the paths did not differ across mothers and fathers. Discussion: The results suggest that mental health is an important dimension that mediates the relationship between parenting stress and dyadic adjustment in the transition to parenthood.